Makna dan interpretasi pragmatis sapaan kayo dalam bahasa Kerinci - Eva Fitrianti; Novi Fitriani (Jurnal Komunitas Bahasa, 2023)
The purpose of this study is to explain the meaning and pragmatic interpretation of the use of the greeting word kayo in the Kerinci language in Koto Baru Village, Tanah Kampung District in order to provide understanding and insight into the meaning of greeting kayo. This research is a descriptive qualitative research. The informants of this study were members of the Desa Koto Baru, Tanah Kampung District, as native speakers of the Kerinci language. Data collection techniques are simak libat cakap techniques, recording techniques, note-taking techniques, and library techniques. The data validation technique uses source and theory triangulation techniques. Data analysis uses data reduction techniques, data presentation, and draws conclusions. The pragmatics meaning in the use of greeting kayo includes literal and nonliteral meanings. The literal meaning shows the intention of the greeter to respect someone who is older than the addressee, while the non-literal meaning intends to respect the addressee for certain purposes. For example, appreciating for having broad insights, as a form of entertaining or joking material, and appreciating for feeling familiar and close. Based on the research results, it is expected that the users of the greeting word kayo can understand its meaning pragmatically and place it according to the context of communication.